Extract of Salvadora persica roots attenuates lead acetate-induced testicular oxidative stress in rats - Gamal A. Soliman; Majid A. Ganaie; Hassan N. Althurwi; Faisal F. Albaqami; Mohammed A. Salkini; Maged S. Abdel-Kader (GarVal Editorial Ltda., 2017)
Context: Lead exerts pathological changes on male mammals. Deleterious effects on testicular tissues may be mediated by oxidative damage and subsequent lipid peroxidation. Medicinal plants can protect against such oxidative stress. Aims: To determine the protective activity of Salvadora persica, against lead acetate (LA) testicular oxidative stress in rats. Methods: Adult male Wistar rats were allocated into six groups: control group received the vehicle, S. persica group received extract (500 mg/kg), LA group was exposed to 0.1% LA in drinking water and three other groups were co-treated with LA plus S. persica (125, 250 and 500 mg/kg). Treatments were applied for 60 days. Five days prior to the end of the experiment, male rats in all groups were mated with untreated females. Results: S. persica (500 mg/kg) increased testosterone level and relative weights of testes, cauda epididymis and seminal vesicles in normal rats but did not affect testicular antioxidant parameters and sperm characteristics. Superoxide dismutase, glutathione peroxidase, catalase activities and the level of reduced glutathione were significantly reduced and malondialdehyde was elevated in the testicular homogenate of LA-exposed rats. LA exposure significantly reduced serum levels of testosterone, follicle-stimulating hormone and luteinizing hormone, as well as, sperm characteristics and relative weight of the testes, cauda epididymis, seminal vesicles and ventral prostate. Administration of S. persica extract (250 and 500 mg/kg) significantly reduced oxidative stress and protected against LA-exposure effects. Conclusions: S. persica extract exhibited marked protective activity against LA-induced testicular oxidative stress in rats.